Regime-switching model of electricity prices for the Philippine energy market - Aspera,Donna Corpuz (Institute of Mathematics, College of Science, University of the Philippines Diliman, 2014)
To date,here has been no adequate model of energy prices in the Philippines. In this paper, a regime-switching approach is used to model the dynamics of electricity spot prices of the Philippine Wholesale Electricity Spot Market. Three regimes are considered to characterize a base regime, an upward spik regime, and a downward spike regime. The parameters of the model are estimated and used to numerically forecast point and interval estimates for a three-month out-of-sample data. The forecasts are then compared with actual realized electricity prices.